COVID-19 and SLE: Infection and autoimmunity at its best - Mahroum, Naim; Elsalti, Abdulrahman; Özkan, Mehmet Fatih; Shoenfeld, Yehuda (SAGE Publications Ltd, 2023)
If one had any doubts before the pandemic regarding the correlation between infections and autoimmunity, COVID-19 left us fascinated on the strong bond between the two entities. The immune and autoimmune reactions seen in patients infected with SARS-CoV-2 have served as a base for this assumption. Later on, the use of immunosuppressants such as systemic glucocorticoids, among other biological agents, turned this assumption to a fact. This was no different when it comes to the vaccines against COVID-19. Through several postulated mechanisms these vaccines, although generally considered safe, are thought to have the potential to result in autoimmune reactions making them not more innocent than the infection itself. When systemic lupus erythematous (SLE) is viewed as a classical autoimmune multisystemic disorder, the connection with SARS-CoV-2 infection and COVID-19 vaccination is of extreme importance. This is because early reports during the pandemic have shown increased rates of SARS-CoV-2 infection among patients known previously to have SLE and much more interestingly, cases of new-onset SLE after COVID-19 have been documented in the literature. Subsequently vaccines against COVID-19, those mRNA-based and adenovirus-vector based, were reported to induce new SLE cases, trigger immune thrombocytopenia or lupus nephritis, two common presentations of SLE, or exacerbate flares. In our paper, we concluded various aspects of available and recent data regarding SLE and COVID-19 as both an infection and vaccination.
Keywords: Autoimmunity; COVID Vaccine; COVID-19; SARS-CoV-2; Systemic Lupus Erythematous